Response to belimumab among patients with systemic lupus erythematosus in clinical practice settings: 24-month results from the OBSErve study in the USA. (11th January 2016) - Collins, C E; Dall'Era, M; Kan, H; Macahilig, C; Molta, C; Koscielny, V; Chang, D J
Abstract : Objective: To examine disease activity and clinical outcomes, and describe overall patterns of systemic lupus erythematosus (SLE) care in patients who received belimumab in a real-world clinical setting. Methods: This observational cohort study was conducted in US clinical practices. Rheumatologists (n=92) identified adults with SLE who had received ≥8 infusions of belimumab plus standard of care (SoC). Physicians assessed disease outcomes at 6-month intervals using patient medical charts, for up to 24 months. The primary outcome was physician-assessed change in SLE disease. Other outcomes included change in steroid use, laboratory tests and healthcare resource utilisation (HCRU). Results: Of 501 patients (intent-to-treat population (ITT)), 446 were female, mean age was 43.3 years and 98% had moderate/severe disease activity at baseline (first dose of belimumab). Data for 277 patients who completed 24 months of belimumab treatment were available. Among the ITT, a ≥50% improvement in overall clinical response between baseline and month 6 was reported for 48.7% of patients; continued improvement was seen at all subsequent 6-month intervals relative to the previous timepoint. The percentage of patients with moderate/severe disease also decreased at each timepoint. At baseline, 77.0% of patients received steroids at a mean (SD) prednisone equivalent dose of 19.9 (14.39) mg/day, which decreased to 8.4 (7.35) mg/day at month 6 and 6.1 (9.31) mg/day at month 24. Abnormal laboratory values typically associated with SLE also demonstrated improvements at month 6, which continued through 24 months. HCRU decreased over the duration of the study. Conclusions: Patients with SLE who received belimumab plus SoC for up to 24 months demonstrated improvements in disease severity and laboratory values and a reduction in steroid use and HCRU as early as month 6. Improvements continued through 24 months, providing evidence of reduced disease activity among patients taking belimumab in real-world clinical practice.